Study of 292 patients for prediction of difficult laparoscopic cholecystectomy using detailed history, clinical and radiological parameters - Agarwal, Dhiraj; Arora, Devansh; Avasthi, Ankur; Kothari, Ankur; Dangayach, K. K. (International Surgery Journal, 2016)
Background: Now laparoscopic Cholecystectomy is one of most commonly performed procedure by General surgeon, and also of very much of interest for trainee to learn basic of laparoscopic procedure. On the basis of history, patient profile, clinical examination and radiological examination, we tried to select the cases that may help to predict the difficult GB. Methods: This study was conducted in Department of General Surgery Mahatma Gandhi Medical College and Hospital, Jaipur from Aug 2013 to Aug 2015 and total 292 enrolled for this study. In our institute we defined DLC according to operating time which was >75 min from incision and veress needle insertion to GB extraction. Results: In our study out of 292 pt we were found 72 pts as difficult GB. Detailed study of these patients clearly shows that pt. of male, higher side of age, increase duration of symptoms with multiple stone which are small in size have more chance of difficulty in laparoscopic Cholecystectomy because these patients have more repeated attacks of cholecystitis silently or clinically detected previously. Conclusions: From this study we conclude that pre-operative radiological investigations (USG, MRCP) are no doubt good predictors of difficult laparoscopic Cholecystectomy in majority of cases and should be used as a screening procedure but more attention should be given to demographic data, history and clinical examination to predict the difficult LC.